Photocatalytic Degradation of Methyl Orange Using TiO2 - Coated Cordierite Substrates: A Comparison of Dip-Coating and Spray-Coating Methods - Trung Hieu Nguyen; Thu Huong Nguyen; Anh-Tuan Vu; Thang Le Minh (Bulletin of Chemical Reaction Engineering & Catalysis, 2025)
In this study, the calcination temperature of TiO2 nanoparticles was investigated at 300, 350, 400, and 450 °C. The results indicated that 400 °C was the optimal calcination temperature, yielding the highest amount of synthesized TiO2 nanoparticles remaining in the anatase phase (97.44 %). TiO2 nanoparticles were coated on cordierite using two methods: spray coating and dip coating. Their characteristics were analyzed and evaluated utilizing several modern techniques. Additionally, their photocatalytic and recovery capabilities were assessed based on methylene orange (MO) degradation efficiency. The spray coating method allowed the TiO2 nanoparticles to evenly cover the cordierite surface, resulting in the highest MO degradation efficiency and best recovery ability. The MO degradation efficiency remained at 83.07 % after 5 reuse cycles. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).